Immune Myocarditis Overlapping With Myasthenia Gravis Due to Anti-PD-1 Treatment for a Chordoma Patient: A Case Report and Literature Review - Liang, Shujing; Yang, Jingxian; Lin, Yun; Li, Tong; Zhao, Wenrong; Zhao, Jun; Dong, Chunyan (Frontiers in Immunology, 2021)
Immunotherapy begins to be widely used due to the increasing exploration and gratifying effects in multiple cancers. Chordoma, as a rare bone malignant tumor, often recurs and metastasizes after undergoing surgery and radiotherapy. Therefore, immunotherapy can be explored as an emerging, potentially effective treatment to improve the survival rate and clinical benefit of patients. However, a variety of immune-related adverse events (irAEs) cannot be avoided completely. And the immunotherapy-induced myocarditis, as a rare but fatal irAE, has been increasingly reported. Understanding the mechanism involved in irAEs can inform best practices for side effects management. Here, we firstly reported a case of immune myocarditis and subsequent myasthenia gravis (MG) following anti-PD-1 treatment for chordoma.